Evaluating the Retreatability of Hydraulic Calcium Silicate-Based Root Canal Sealer Using Root Canal Instrumentation—An In Vitro Study - Akanksha Malik; Anjali Kothari; Charmi Mehta; Vinay Rao; Kavita Sule; Deep Agrawal; Priyal Patel (Journal of Pharmacy and Bioallied Sciences)
Aim: This study aimed to compare the retreatability of hydraulic calcium silicate-based (HCSB) and epoxy resin-based sealers in single-rooted mandibular premolars, with a specific focus on sealer remnants and retreatment duration. Methodology: Sixty mandibular premolars were biomechanically prepared and obturated with BioRoot RCS, MTA Fillapex, or AH Plus. After a one-month period, the gutta-percha was removed and the specimens were analyzed under a stereomicroscope. Result: BioRoot RCS showed the most remnants and longest retreatment time, while AH Plus was the most efficient. Conclusion: BioRoot RCS is less favorable for retreatment, with AH Plus being the most effective.